Osteopontin neutralisation abrogates the liver progenitor cell response and fibrogenesis in mice. Issue 7 (5th June 2014) - Coombes, J D; Swiderska-Syn, M; Dollé, L; Reid, D; Eksteen, B; Claridge, L; Briones-Orta, M A; Shetty, S; Oo, Y H; Riva, A; Chokshi, S; Papa, S; et al.
Abstract : Background: Chronic liver injury triggers a progenitor cell repair response, and liver fibrosis occurs when repair becomes deregulated. Previously, we reported that reactivation of the hedgehog pathway promotes fibrogenic liver repair. Osteopontin (OPN) is a hedgehog-target, and a cytokine that is highly upregulated in fibrotic tissues, and regulates stem-cell fate. Thus, we hypothesised that OPN may modulate liver progenitor cell response, and thereby, modulate fibrotic outcomes. We further evaluated the impact of OPN-neutralisation on murine liver fibrosis. Methods: Liver progenitors (603B and bipotential mouse oval liver) were treated with OPN-neutralising aptamers in the presence or absence of transforming growth factor (TGF)-β, to determine if (and how) OPN modulates liver progenitor function. Effects of OPN-neutralisation (using OPN-aptamers or OPN-neutralising antibodies) on liver progenitor cell response and fibrogenesis were assessed in three models of liver fibrosis (carbon tetrachloride, methionine-choline deficient diet, 3, 5, -diethoxycarbonyl-1, 4-dihydrocollidine diet) by quantitative real time (qRT) PCR, Sirius-Red staining, hydroxyproline assay, and semiquantitative double-immunohistochemistry. Finally, OPN expression and liver progenitor response were corroborated in liver tissues obtained from patients with chronic liver disease. Results: OPN is overexpressed by liver progenitors in humans and mice. In cultured progenitors, OPN enhances viability and wound healing by modulating TGF-β signalling. In vivo, OPN-neutralisation attenuates the liver progenitor cell response, reverses epithelial-mesenchymal-transition in Sox9+ cells, and abrogates liver fibrogenesis. Conclusions: OPN upregulation during liver injury is a conserved repair response, and influences liver progenitor cell function. OPN-neutralisation abrogates the liver progenitor cell response and fibrogenesis in mouse models of liver fibrosis.